Bis{ N 2 , N 6 -bis[(pyridin-3-yl)methyl]pyridine-2,6-dicarboxamide-κ N }bis(methanol-κ O )bis(thiocyanato-κ N )cobalt(II) - Yang, Guang-Rui; Ren, Juan; Li, Guo-Ting (Acta crystallographica. Section E, Structure reports online, 2012)
In the title compound, [Co(NCS) 2 (C 19 H 17 N 5 O 2 ) 2 (CH 3 OH) 2 ], the Co II atom lies on an inversion center and is coordinated by two isothiocyanate N atoms, two O atoms of methanol molecules and two pyridine N atoms in a slightly distorted octahedral environment. Intermolecular O—H...O and N—H...N hydrogen bonds join the complex molecules into layers parallel to the bc plane.